Additions and corrections to taxonomy of Apobaetis fiuzai Salles & Lugo-Ortiz, 2002 and Apobaetis kallawaya Nieto, 2006 (Ephemeroptera, Baetidae) - De Lima, Cláudia R.T.; Cruz, Paulo Vilela; Hamada, Neusa (European Journal of Taxonomy, 2023)
Recently, it has been hypothesized that the wide distribution of A. fiuzai Salles & Lugo-Ortiz is due to a wide diagnosis and conflicting keys. The same arguments can be applied to A. kallawaya Nieto. In order to test this hypothesis, we revised the type material of A. fiuzai, literature of A. kallawaya, and part of the recorded specimens in Brazil. As a result, three new species from previous records are recognized: Apobaetis pasternakae sp. nov., former A. fiuzai in Amazonas, Roraima and Maranhão states; Apobaetis jaquelinae sp. nov., former A. fiuzai in Rondônia State; Apobaetis luanae sp. nov., former A. kallawaya in Rondônia State. The new data showed that A. fiuzai does not occur in the Amazon Biome and A. kallawaya does not occur in Brazil. Records of A. fiuzai that could not be reviewed in this study are treated as putative and should be evaluated in the light of the new evidence. We also studied the intraspecific variation in A. fiuzai and A. pasternakae sp. nov. The pigment pattern of the nymphs was not considered a robust characteristic for the species differentiation due to the wide variation in and between populations, and interspecific similarity of many features. On the other hand, classical morphological characters such as mouthparts, legs, spines of terga, paraproct and caudal filaments have minimal variation, stable and reliable for specific identification.